Generation of Carbamic Acid (NH2CO2H) and its Radical Cation as Stable Species in the Gas Phase - Klaas Jan van den Berg; Carlito B. Lebrilla; Johan K. Terlouw; Helmut Schwarz (CHIMIA)
Thermolysis of ammonium carbamate yields the hitherto unknown free carbamic acid (H2N–CO–OH), which is characterized by means of mass spectrometric methods. In the gas phase high energy barriers prevent the spontaneous dissociation of both neutral carbamic acid (1) and its radical cation (1⊕⨀).